Análisis bibliográfico de la influencia de la poesía de J. C. F. Schiller en España a través de traducciones al castellano. - Galán, Ilia (Revista General de Información y Documentación, 2000)
This paper presents a critical analysis of the complete bibliography in the spanisch language, up to 2000, of Friedrich Schiller's poetry. Schiller was, with Goethe, the most representative of the German Romantic movement. Rut it was not until the 1950's tbat bis poems, albeit in poor translations, be gan to be known. We have not quality publications; only his theatre it's alí well transíated. Bis poetry is waiting a complete publication with a correctly transíation.
Keywords: Schiller; bibliography; translations; Romanticisin; German Poetry